Hydrologic ecosystem services: water quality and quantity in the Magdalena River, Mexico City - Jujnovsky, Julieta; Almeida-Leñero, Lucia; Bojorge-García, Miriam; Monges, Yani Laura; Cantoral-Uriza, Enrique; Mazari-Hiriar, Marisa (HIDROBIOLÓGICA, 2017)
The increasing urbanization in big cities, that jeopardizes the ecosystems, makes it important to protect them as well as to recognize and manage the services they provide. In order to have the required scientific evidence to support conservation projects, an assessment of water quality and quantity seen as hydrological ecosystem services in the Magdalena River watershed, was carried out. Water quality was assessed in two annual cycles based on physicochemical, chemical, bacteriological and algal indicators, showing an abrupt change between the natural and urbanized areas. This has the potential to affect negatively the recreational activities practised in the area. The relevance of the indicators for water quality is that they show different aspects of the problem: physical and chemical parameters indicate variations across sites along the Magdalena River and point the places where domestic discharges occur. Algae reveal the natural conditions of the habitat and the risks to public health can be assessed with bacteriological indicators. To calculate the water quantity, balances were made in order to know the amount of water that runoff in the three dominant plant communities: the fir forest that generates 10,944,800 m3 of water per year, the pine forest generates 6,878,000 m3 and the mixed and oak forest generates 3,217,500 m3 . It is important to preserve the hydrological ecosystem services conserving the forests and rehabilitating the Magdalena River in order to enhance the provision of drinking water to the southern part of Mexico City.